Alcohol use, expectancies and HIV-related sexual risk: a cross-sectional survey of male migrant workers in South India. Issue 5 (4th May 2018) - Steward, Wayne T.; Satyanarayana, Veena A.; Heylen, Elsa; Srikrishnan, Aylur K.; Vasudevan, Canjeevaram K.; Krishnan, Gopal; Solomon, Davidson; Ekstrand, Maria L.
ABSTRACT: Male migrant workers (MMWs) in India are vulnerable to developing alcohol-related problems and engaging in unprotected sex, putting them at risk of HIV. Research has shown that alcohol-related expectancies mediate vulnerability to alcoholism. We examined which expectancies were associated with sexual risk and drinking. We surveyed 1085 heterosexual MMWs in two South Indian municipalities, assessing expectancies, sex under the influence, and unprotected sex with female sex workers (FSW) and casual female partners in the prior 30 days. Men more strongly endorsed positive than negative expectancies ( t  = 53.59, p  < .01). In multivariate logistic regression, the expectancy of having more fun helped drive the combination of alcohol and unprotected sex with FSW partners (OR = 1.22, p  < .05), whereas the expectancy of better sex helped drive a similar combination with casual partners (OR = 1.24, p  < .01). Men concerned about alcohol-induced deficits were less likely to drink with FSW partners (OR = 0.81, p  < .01), but more likely to have unprotected sex with them (OR = 1.78, p  < .01). To reduce risk, MMWs would benefit from combination prevention approaches that use behavioral strategies to address drinking norms and awareness of risk, while using biomedical strategies to reduce viral transmission when risk does occur.